2021
DOI: 10.1097/wnn.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia Induced by Infratentorial Ischemic Stroke: Two Case Reports

Abstract: Aphasia induced by an infratentorial stroke has rarely been reported, and its mechanism has not been fully identified. We evaluated two individuals who had been admitted to Saiseikai Kumamoto Hospital in Kumamoto, Japan, due to acute ischemic stroke in order to determine whether their aphasia was induced by an infratentorial stroke. The first patient, a 59-year-old man with a history of left parietal embolic stroke with very mild sequelae of anomia, developed Wernicke’s aphasia, nonfluent speech, and right lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Language information is introduced into Wernicke area and processed and transmitted to Broca area by arcuate fiber bundle. Finally, Broca area processes the information and transforms it into language activities [ 16 ]. Most scholars believe that speech disorders caused by lesions in different parts of the left cerebral hemisphere have their own characteristics, including Broca aphasia caused by damage to the Broca area in the posterior part of the left inferior frontal gyrus, Wernicke aphasia caused by damage to the Wernicke area in the posterior part of the temporal transverse gyrus of the auditory cortex, conductive aphasia caused by damage to the projection fibers or arcuate bundles between the temporal-parietal and frontal lobes, and complete aphasia caused by Broca area, Wernicke area, basal ganglia area, and insula damage [ 17 19 ].…”
Section: Poststroke Aphasiamentioning
confidence: 99%
“…Language information is introduced into Wernicke area and processed and transmitted to Broca area by arcuate fiber bundle. Finally, Broca area processes the information and transforms it into language activities [ 16 ]. Most scholars believe that speech disorders caused by lesions in different parts of the left cerebral hemisphere have their own characteristics, including Broca aphasia caused by damage to the Broca area in the posterior part of the left inferior frontal gyrus, Wernicke aphasia caused by damage to the Wernicke area in the posterior part of the temporal transverse gyrus of the auditory cortex, conductive aphasia caused by damage to the projection fibers or arcuate bundles between the temporal-parietal and frontal lobes, and complete aphasia caused by Broca area, Wernicke area, basal ganglia area, and insula damage [ 17 19 ].…”
Section: Poststroke Aphasiamentioning
confidence: 99%
“…Inatomi et al reported a patient with infratentorial infarction who developed aphasia after recovering from a speech disturbance due to left parietal lobe infarction. They hypothesized that disruption of the compensatory intensi cation of the crossed cerebellocerebral pathway caused by the initial infarction may be associated with infratentorial stroke-induced aphasia [4]. However, detailed information about the symptoms of speech disturbance due to the initial infarction was not provided in the report.…”
Section: Introductionmentioning
confidence: 99%
“…Crossed cerebellar diaschisis (CCD), firstly reported in cerebral infarction patients, was defined as coupled hypometabolism and hypoperfusion in the cerebellar hemisphere contralateral to the supratentorial lesions ( Baron et al, 1981 , Sebök et al, 2021 ). In addition to the ataxic hemiparesis, cerebellar dysfunction within CCD may be involved in the abnormal posture, shoulder subluxation, and impairment of non-motor functions as well ( Chang et al, 2017 , Hsieh et al, 2020 , Inatomi et al, 2021 , Kwon et al, 2015 , Nishida et al, 2019 , Yoshida et al, 2018 ). Consequently, more extensive investigations are required for the better intervention of CCD and its associated comorbidities.…”
Section: Introductionmentioning
confidence: 99%